Diarrhoea: interventions, consequences and epidemiology in the intensive care unit (DICE-ICU): a protocol for a prospective multicentre cohort study. Issue 6 (27th June 2019) - Dionne, Joanna C; Sullivan, Kristen; Mbuagbaw, Lawrence; Takaoka, Alyson; Duan, Erick Huaileigh; Alhazzani, Waleed; Devlin, John W; Duprey, Matthew; Moayyedi, Paul; Armstrong, David; Thabane, Lehana; Tsang, Jennifer L Y; et al.
Abstract : Introduction: Diarrhoea is a frequent concern in the intensive care unit (ICU) and is associated with prolonged mechanical ventilation, increased length of ICU stay, skin breakdown and renal dysfunction. However, its prevalence, aetiology and prognosis in the critically ill have been poorly studied. The primary objectives of this study are to determine the incidence, risk factors and consequences of diarrhoea in critically ill adults. The secondary objectives are to estimate the incidence of Clostridium difficile- associated diarrhoea (CDAD) in ICU patients and to validate the Bristol Stool Chart and Bliss Stool Classification System characterising bowel movements in the ICU. Our primary outcome is the incidence of diarrhoea . Our secondary outcomes include: CDAD, ICU and hospital mortality and ICU and hospital length of stay. Methods and analysis: This international prospective cohort study will enrol patients over 10 weeks in 12 ICUs in Canada, the USA, Poland and Saudi Arabia. We will include all patients 18 years of age and older who are admitted to the ICU for at least 24 hours and follow them daily until ICU discharge. Our primary outcome is the incidence of diarrhoea based on the WHO definition, during the ICU stay. Our secondary outcomes include: CDAD, ICU and hospital mortality and ICU and hospital length of stay. We will use logistic regression to identify factors associated with diarrhoea (as defined using WHO criteria) and the kappa statistic to measure agreement on diarrhoea rates between the WHO definition and the Bristol Stool Chart and Bliss Stool Classification System. Ethics and dissemination: The protocol has been approved by the research ethics board of all participating centres. The diarrhoea interventions, consequences and epidemiology in the intensive care unit (DICE-ICU) study will generate evidence about diarrhoea and its frequency, predisposing factors and consequences, to inform critical care practice and future research. Lay summary: Diarrhoea is a frequent clinical problem for hospitalised patients including those who are critically ill in the ICU. Diarrhoea can cause complications such as skin damage, dehydration and kidney problems. It is not clear how common diarrhoea is in the ICU, the factors that cause it or the best way for clinicians to assess it. The DICE-ICU study is an international prospective observational study to examine the frequency, risk factors and outcomes of diarrhoea during critical illness.